Penyuluhan dan Skrining Hepatitis B pada Ibu Hamil dengan Rapid Tes Di Kecamatan Kediri Kabupaten Tabanan Tahun 2018 - I Gusti Ayu Sri Dhyanaputri; Cok Dewi Widya hana Sundari; I Nyoman Mastra; I Nyoman Jirna; I A.M. Sri Arjani; I Wayan Merta; I G. Sudarmanto; I G.A. Dewi sarihati (Poltekkes Kemenkes Denpasar, 2019)
Hepatitis B Virus can be transmitted by pregnant women to the fetus during labor. Therefore Hepatitis B examination during pregnancy is very necessary to find out whether during pregnancy pregnant women are infected with the Hepatitis B virus or not, so prevention can be done immediately. The purpose of this community service activity is to determine hepatitis B infection in pregnancy through HBsAg and Anti-HBs examination with a rapid test in Kediri District. The Community service activities is done by HBsAg and Anti HBs examination with Rapid Test, and provide counseling about Hepatitis B in pregnant women. Results of this community service showed from 100 pregnant women, obtained the age of of pregnant women 26-30 years (32%), the highest gestational age are 7 months (21%), the highest number of gravidas was gravida 2 (47%). Knowledge about Hepatitis B after counseling is 92% of knowledge in good category. 6% of pregnant women were infected with the Hepatitis B virus.Keywords: Hepatitis B, Pregnant Woman, Hepatitis B Screening.